The Annual Modulation Signature for Dark Matter: DAMA/LIBRA-Phase1 Results and Perspectives - Rita Bernabei; Pierluigi Belli; Fabio Cappella; Vincenzo Caracciolo; Simone Castellano; Riccardo Cerulli; Chang Jang Dai; Annelisa d’Angelo; Silio d’Angelo; Alessandro Di Marco; H. L. He; Antonella Incicchitti; et al. (Advances in High Energy Physics)
The results obtained with the total exposure of 1.04 ton × yr collected by DAMA/LIBRA-phase1 deep underground at the Gran Sasso National Laboratory (LNGS) of the I.N.F.N. during 7 annual cycles are summarized. The DAMA/LIBRA-phase1 and the former DAMA/NaI data (cumulative exposure 1.33 ton × yr, corresponding to 14 annual cycles) give evidence at 9.3 σ C.L. for the presence of Dark Matter (DM) particles in the galactic halo, on the basis of the exploited model independent DM annual modulation signature by using highly radiopure NaI(Tl) target. The modulation amplitude of the single-hit events in the (2–6) keV energy interval is 0.0112±0.0012 cpd/kg/keV; the measured phase is 144±7 days and the measured period is 0.998±0.002 yr; values are in a good well in agreement with those expected for DM particles. No systematic or side reactions able to mimic the exploited DM signature have been found or suggested by anyone over more than a decade. Some of the perspectives of the presently running DAMA/LIBRA-phase2 are outlined.